The Effect of Sustainability Orientation, Green Innovation, and Corporate Social Responsibility on Firm Reputation - Eko Cahyo Mayndarto; Hilda Yuliastuti; Iriana Bakti; Dahlia (Journal Management & Economics Review (JUMPER), 2026)
In the modern business environment, corporate reputation has become a crucial intangible asset that influences stakeholder trust, competitive advantage, and long-term organizational sustainability. Companies are increasingly expected to demonstrate commitment to environmental responsibility, sustainable innovation, and social contribution. Therefore, this study aims to examine the effect of sustainability orientation, green innovation, and corporate social responsibility on firm reputation. This research employs a quantitative approach using survey data collected from 200 managers and senior employees working in companies that implement sustainability-related practices. The data were collected through structured questionnaires using a five-point Likert scale. The sampling technique used in this study was purposive sampling to ensure that respondents had sufficient knowledge regarding sustainability initiatives within their organizations. The data were analyzed using multiple linear regression analysis to evaluate the relationships between the independent variables and firm reputation. The results of the analysis show that sustainability orientation has a positive and significant effect on firm reputation, indicating that companies that integrate sustainability principles into their strategic decision-making processes tend to gain higher levels of stakeholder trust and credibility. Green innovation is also found to have a positive and significant influence on firm reputation, suggesting that organizations that develop environmentally friendly products, technologies, and production processes are perceived more positively by stakeholders. Furthermore, corporate social responsibility demonstrates the strongest positive effect on firm reputation among the variables examined in this study. This finding indicates that companies that actively engage in CSR initiatives such as community development, environmental protection, and ethical business practices are more likely to enhance their corporate image and public trust. Overall, the findings highlight the importance of sustainability-related strategies in strengthening firm reputation in today's competitive business environment. Organizations that integrate sustainability orientation, promote green innovation, and implement effective CSR initiatives can build stronger relationships with stakeholders and improve their long-term reputation and competitiveness. These findings provide valuable insights for managers and policymakers regarding the strategic role of sustainability practices in enhancing corporate reputation and organizational sustainability.